HUBUNGAN PENGETAHUAN GIZI TERHADAP KONSUMSI SAYUR DAN BUAH REMAJA PUTRI SMPIT AL – FITYAN BOARDING SCHOOL KUBU RAYA - Naomi Oktivaner Panjaitan; Sopiyandi; Jonni Syah R.Purba (Media Gizi Khatulistiwa, 2025)
Background: Indonesia is a region rich in natural resources such as fruit and vegetables. Fruit and vegetables contain the nutrients vitamins, minerals and fiber to fulfill a balanced nutritional diet. Consuming enough fruit and vegetables can maintain blood pressure, blood sugar levels and blood cholesterol at normal levels, and reduce the risk of difficulty defecating (constipation) and obesity. One of the factors that influences fruit and vegetable consumption in children is nutritional knowledge. Objective: To determine the relationship between nutritional knowledge and vegetable and fruit consumption among adolescent girls at SMPIT Al-Fityan School Kubu Raya Method: This research uses a cross-sectional approach. The respondents used were teenage girls at Al-Fityan Boarding School Kubu Raya using a simple random sampling technique. The total research sample was 61 respondents. The research measuring tool uses a nutritional knowledge questionnaire, recall 2 x 24 H. Result: Shows that the nutritional knowledge of female teenagers at Smpit Al-Fityan Boarding School Kubu Raya is in the sufficient category as many as 35 respondents (57.4%) and nutritional knowledge in the good category as many as 21 respondents (34.4%). Consumption of vegetables and fruit among young women at SMPIT AL-Fityan Boarding School Kubu Raya. Fruit consumption in the good category was 29 respondents (47.5%) and in the poor category was 32 respondents (52.5%). However, vegetable consumption is still categorized as insufficient, namely 47 respondents (77%) consume <250g/day of vegetables. The research results showed that there was no relationship between nutritional knowledge and vegetable and fruit consumption ( sig 0,05). Conclusion : There is no relationship between nutritional knowledge and fruit and vegetable consumption (p value = 0.138, p value = 0.775)